Pengaruh Lingkungan Kerja Dan Motivasi Terhadap Disiplin Kerja Karyawan Di Hotel Balairung Jakarta - Ifrah Galbina; Hijriyantomi Suyuthie (Universitas Katolik Widya Karya Malang, 2023)
This research aims to determine the influence of the work environment and motivation on employee work discipline at Hotel Balairung Jakarta. The method used in the research is a quantitative method with a causal associative approach. The respondents in the research population were all employees of Hotel Balairung Jakarta with a sample size of 62 respondents. Data collection is carried out by filling out questionnaires or questionnaires which have been prepared using a Likert scale. To test the hypothesis, multiple linear regression analysis was used. The research results show that work environment variables do not have a significant effect on work discipline, while motivation variables have a significant effect on work discipline. But together the work environment and motivation variables have a significant effect on work discipline.